Muzyczność we współczesnym misterium na przykładzie dramatu Roberta Lewandowskiego "Pustynia. Misterium na dwóch starców i chorał" - Antczak-Zajdel, Aleksandra (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2009)
The article presents brief historical description of miracle play and choral and their development of throughout centuries. What is more, it delineates connections between contemporary dramatic forms and genie traditions. The author concentrates on the musical elements and their functions in the process of creation of literary work and characters. It presents the correspondence literary and musical works.